Factors associated with the recurrence of choroidal neovascularization in pathologic myopia - Jing, Ruixia; Bo, Yuxia; Gao, Lei; Wang, Zhen (Frontiers in Medicine, 2022)
Abstract Purpose: To investigate the factors associated with the recurrence of pathologic myopia choroidal neovascularization (PM-CNV). Methods: Forty-eight eyes of 48 patients with PM-CNV treated with conbercept at least 6 months of follow-up were included. Appearance of ellipsoid zone (EZ) and retinal pigment epithelium (RPE) observed on optical coherence tomography (OCT). Hyperreflective foci (HRF) height measured on OCT. Observation of CNV shape on OCT-angiography (OCTA). PM-CNV area measured on OCTA. To observe relationship between these factors and best corrected visual acuity (BCVA) and PM-CNV recurrence. Results: The 48 patients (48 eyes) with PM-CNV were divided into two groups: yielding a group of 20 eyes with type 1 and a group of 28 eyes with type 2. The BCVA of type 1 was better than type 2 before and after treatment (P < 0.005). Smaller HRF height (P < 0.001) and CNV area (P < 0.001) for type 1 than type 2. The appearance of EZ and RPE were intact (P < 0.001). Spearman correlation analysis found that final BCVA was significantly associated with baseline BCVA, HRF height, and appearance of EZ (P < 0.05). Binary logistics regression analysis revealed that PM-CNV recurrence was significantly correlated not only HRF height and CNV area, but also with appearance of EZ, and RPE (P < 0.05). Conclusion: PM-CNV had a higher recurrence ratio. Baseline BCVA and clinical features play an important role for vision prognosis. Factors associated with PM-CNV recurrence include HRF height, CNV area, and changes in EZ and RPE structure.